The Conversations About Cancer (CAC) Project—Phase II: National findings from viewing When Cancer Calls…and implications for Entertainment–Education (E–E). Issue 3 (March 2016) - Beach, Wayne A.; Dozier, David M.; Buller, Mary K.; Gutzmer, Kyle; Fluharty, Lyndsay; Myers, Valerie H.; Buller, David B.
Highlights: When Cancer Calls …is an innovative theatrical production. Drawn from the first natural history of actual family phone conversations. Significant national impacts for cancer patients, survivors, and family members. Powerful triggering device for addressing delicate and complex cancer topics. A new genre of Entertainment–Education for national and global education. Abstract: Objective: We address cancer communication by creating and assessing the impacts of a theatrical production, When Cancer Calls… ( WCC… ), anchored in conversations from the first natural history of a patient and family members talking through cancer on the telephone. Methods: A national study was conducted using a multi-site and randomized controlled trial. An 80-minute video was produced to assess viewing impacts across cancer patients, survivors, and family members. Comparisons were made with a control video on cancer nutrition and diet. Pretest–posttest sample size was 1006, and 669 participants completed a 30-day follow-up impacts assessment. Results: All five family and communication indices increased significantly for WCC… . When compared to the placebo, average pretest–posttest change scores were higher for self-efficacy (775%), family fabric (665%), outside support (189%), and family communication (97%). One month following viewings, WCC… participants reported 30% more conversations about cancer among patients and family members about cancer. Conclusion: A new genre of Entertainment–Education (E–E) was created that triggers positive reactions from audience members. Managing delicate and often complex communication about the trials, tribulations, hopes, and triumphs of cancer journeys is fundamentally important for everyday living. Practice implications: Unique opportunities exist to make WCC… available to national and global audiences, create tailored curricula, and integrate these viewings into educational programs for patients, family members, and care-provider teams across diverse health, corporate, and governmental systems.